Análise crítica da NBR ISO 9001:2000 x NBR 6118:2003 para aprovação de execução de estruturas de concreto armado - Nunes, Harlen (Universidade Federal de São Carlos, 2011)
This work shows the methodology for standardization of quality programs like NBR ISO 9001:2000 employed in construction of reinforced concrete structure for multi floor building, and relationship of this standard to the NBR 6118:2003 and 14931 NRB, governing the requirements and methodology for design and execution of concrete structures. It was, therefore, present the main recommendations of ISO 6118:2003 and NBR14931 interface with the NBR ISO 9001:2000 standard procedure for receiving approval of reinforced concrete structures. This work was conceived through a methodology of presenting guideline of quality programs and standards pertaining to the concrete, trying to match the tables and guidelines used for verification of services advocated by quality programs, with the technical regulations defined by the rules. And finally, proposes a new type of design for these checks and standards proposed by quality programs so now rendered compatible with the requirements of the standards that define and guide the design, implementation and receipt of reinforced concrete structures. This new design is done through a simple check with the help of tables which ensure that standards are met will the project level, performance and visual appearance of this structure.
Critical analysis of NBR NBR ISO 9001:2000 X NBR 6118:2003, for approval of implementation of concrete structures
Keywords: Concreto armado; ISO 9001; NBR ISO 9000; NBR 6118:2003; Concrete structure; NBR ISO 9001:2000; NBR 6118:2003; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL